Effects of Chinese medicines on monacolin K production and related genes transcription of Monascus ruber in red mold rice fermentation. Issue 4 (17th March 2020) - Peng, Lin; Ai‐lati, Aisikaer; Liu, Shuangping; Ji, Zhongwei; Mao, Jian; Che, Xin
Abstract: Monacolin K (MK) is a secondary metabolite synthesized by polyketide synthases of Monascus spp. In this study, the combined supplementation of three medicines, including Citri Reticulatae Pericarpium (CRP), Fructus crataegi (FC), and Radix Angelicae Dahuricae (RAD), were mixed with nonglutinous rice and were optimized by response surface methodology to enhance the production of MK in fermented red mold rice (RMR). Under the optimum condition, MK production achieved 3.60 mg/g, which was 41.18% higher than RMR without medicines. The improved MK production was mainly caused by the up‐regulated transcription level of mokA, mokB, mokF, mokH, mokI, and mplaeA . Meanwhile, the inhibitory effect of Poria cocos (PC) on MK production (only 0.436 mg/g) was caused by significantly down‐regulated transcription of six tested genes. Therefore, this study is beneficial for better understanding of the possible mechanism of enhanced MK production by optimization of fermentation conditions. Abstract : Mixed three Chinese traditional medicines enhanced monacolin K production in solid‐state fermentation of red mold rice. The possible mechanism may be attributed to the regulation of expression of genes related to MK synthesis.